2003
DOI: 10.1108/02630800310507159
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behaviour of concrete beams internally reinforced with GFRP rods and steel rebars

Abstract: Use of fibre‐reinforced polymer (FRP) composite rods, in lieu of steel rebars, as the main flexural reinforcements in reinforced concrete (RC) beams have recently been suggested by many researchers. However, the development of FRP RC beam design is still stagnant in the construction industry and this may be attributed to a number of reasons such as the high cost of FRP rods compared to steel rebars and the reduced member ductility due to the brittleness of FRP rods. To resolve these problems, one of the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 11 publications
0
56
0
2
Order By: Relevance
“…A gradual increment is applied to the normalized tensile strain at the concrete bottom fibre ( β ), and corresponding values of the normalized compressive strain at the concrete top fibre ( λ ), and the normalized tensile strain of the steel (ψ ) and FRP (ν ) are obtained from Eqs. (10) to (12).…”
Section: Closed-formulation To Determinate the Moment-curvature Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A gradual increment is applied to the normalized tensile strain at the concrete bottom fibre ( β ), and corresponding values of the normalized compressive strain at the concrete top fibre ( λ ), and the normalized tensile strain of the steel (ψ ) and FRP (ν ) are obtained from Eqs. (10) to (12).…”
Section: Closed-formulation To Determinate the Moment-curvature Responsementioning
confidence: 99%
“…In an attempt of overcoming these drawbacks, some researchers [10][11][12][13] proposed a combination of FRP and steel reinforcements for concrete beams. Combining these reinforcement materials and considering the minor concrete cover required for FRP, an effective reinforcement solution in terms of durability is obtained by placing the FRP bars near the outer surface of the tensile zone, and steel bars at an inner level of the tensile zone (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in stiffness was reported for hybrid beams with steel bars placed above the AFRP bars. Leung and Balendran [14] investigated the flexural response of hybrid concrete beams reinforced with glass FRP (GFRP) and steel bars placed at different levels. The authors reported that the hybrid-reinforced beams had higher flexure strength than the steel-or GFRP-reinforced beams.…”
Section: Introductionmentioning
confidence: 99%
“…However, the major obstacles of the application of FRP bars as a reinforcing material for concrete structures are the relatively high initial costs, low modulus of elasticity, lack of ductility (linear stress-strain diagram up to rupture with no discernible yield point), and absence of well-consolidated design guidelines [2][3][4]. Concrete members reinforced with FRP and subjected to bending moments behave linearly up to cracking, and almost linearly after cracking with a significant lower stiffness [5,9]. Deflections and strains of concrete members reinforced with FRP bars are generally larger than the homologous members reinforced with steel bars.…”
Section: Introductionmentioning
confidence: 99%